Acoustomagnetic detection of magnetic nanoparticles in a model - Bondarenko, I. S.; Аврунін, О. Г.; Gryshkov, O.; Glasmacher, B.; Bondarenko, S. I.; Krevsun, A. V.; Rakhimova, M. V. (The International Journal of Artificial Organs, 2019)
Magnetic nanoparticles (MNPs) are used in medicine for targeted drug delivyry to the area of the cancer. The installation consists of the ultrasound generator, the permanent magnet, the glass containerwith the colloidal mixture, the multi-turn coil about of the glass tube and the voltmeter. The experimental result corrilates with the calculated ones. It is suggested that AMM can used to detect MNPs in the real biological substance.
Keywords: magnetic nanoparticles; biological substance; colloidal solution; ultrasound; magnetic field